Global trends in chronic thromboembolic pulmonary hypertension clinical trials and dissemination of results. (1st November 2021) - McInnis, Micheal C.; Chow, Clement T.; Boutet, Alexandre; Mafeld, Sebastian; Granton, John; McRae, Karen; Donahoe, Laura; de Perrot, Marc
Abstract : Treatment options for chronic thromboembolic pulmonary hypertension (CTEPH) are rapidly expanding. The purpose of this study is to identify trends in CTEPH clinical trials and the publication of results. We performed a worldwide review of completed and ongoing clinical trials through searching the ClinicalTrials.gov database and the World Health Organization International Clinical Trials Registry Platform for "CTEPH" and related terms. Entries were classified as pharmaceutical/procedural interventions (Group 1), all other clinical trials (Group 2) and patient registries (Group 3). Trial characteristics and national affiliation were recorded. PubMed was searched for related publications. There were 117 clinical trials registry entries after removing duplicates and non‐target records. Group 1 comprised 29 pharmaceutical, 15 procedural, and four combined interventions starting in 2005, 2010, and 2016, respectively. Riociguat and balloon pulmonary angioplasty were the most frequent pharmaceutical and procedural interventions, respectively. The proportion of procedural trials increased over time from 0% of those in 2005–2009 to 29% in 2010–2014 and 54% in 2015–2020. There were 56 entries in Group 2 and 13 in Group 3. Japan was the most frequent national affiliation and the most frequent participating country, present in 28% of all trials. The proportion of entries with published results was highest with Group 3 (62%) and lowest with Group 1 (27%). Thirty percent of all publications occurred in 2020. In conclusion, CTEPH clinical trials are increasingly procedural based, with growth largely attributable to Japan and balloon pulmonary angioplasty. Most trials have not published, but results from balloon pulmonary angioplasty clinical trials are anticipated soon.